Granular control of photovoltaic arrays by means of a multi‐output Maximum Power Point Tracking algorithm. (22nd March 2012) - Petrone, Giovanni; Ramos‐Paja, Carlos Andrés; Spagnuolo, Giovanni; Vitelli, Massimo
ABSTRACT In this paper, a Distributed Maximum Power Point Tracking (D‐MPPT) approach in photovoltaic (PV) applications is discussed. The proposed control method is suitable for the granular control of the PV generator at a module level or even at a sub‐module level. D‐MPPT is usually implemented by means of independent converters, each one of them running its own MPPT algorithm. Instead, the architecture proposed in this paper consists of only one digital controller, implementing a multivariable MPPT algorithm based on the Perturb and Observe approach, acting on a number of dc/dc converters, each one of them dedicated to a single PV module. The proposed control strategy reduces the number of current sensors with respect to the classical D‐MPPT architecture and tracks the maximum power evaluated at the dc/dc converters' output. Planar solid immersion mirror simulations and experimental results confirm the validity of the approach and of the design guidelines proposed in the paper. Copyright © 2012 John Wiley & Sons, Ltd.